First-Principle Study of H2 Adsorption on LaFeO3(110) Surface. (21st July 2014) - Chen, Yu-Hong; Zhang, Bing-Wen; Yang, Liang; Zhang, Mei-Ling; Zhang, Cai-Rong; Kang, Long; Luo, Yong-Chun
Abstract : The adsorption of H2 molecule on LaFeO3 (110) surface was studied by first-principle calculations. Based on the adsorption sites, adsorption energies, and electronic structures, it can be found that one H atom can be adsorbed on O atom and form –OH with the O atom, which is the most stable structure. One H atom can be adsorbed on one Fe atom, which makes Fe 3+ turn to Fe 2+ . Two H atoms can form H2 O molecule with O atom, which makes it possible to form oxygen vacancy on the surface.